A Molecular Dynamic approach to the differential interaction between unsaturated free fatty acids and the nicotinic acetylcholine receptor - Obiol, Diego Javier (2019)
Free fatty acids (FFAs) are important cellular components that increase under certainpathological conditions. One of the effects of FFAs is a protection mechanism through themodulation of ion channels. The activity of the nicotinic acetylcholine receptor (nAchR) isblocked by certain FFAs and its binding site is located at the lipid-protein interface. Theobjective of this work was to determine, by means of molecular dynamics (MD), thepossible points of contact and the effect produced by five different FFAs, located inannular and non-annular sites. The study was carried out on a system composed by amodel of AChR from Torpedo marmorata (PDB ID: 2BG9) that was elaborated from PDBID: 4COF as a template because the e-values were the lowest for each subunit andbecause it represented the closed desensitized state. The evaluation of thestereochemical parameters for the refined model was improved with respect to 2BG9.The refined model was incorporated into a lipid bilayer composed with a ratio of 1:1:3 ofcholesterol, POPA and POPC respectively. We replaced three phospholipids from the lipidbilayer with three of the corresponding free fatty acids: cis-18:1ω-6, cis-18:1ω-9,cis-18:1ω-11, cis-18:1ω-13 and trans-18:1ω-9 in annular or non-annular areas. From theMD runs we obtained the most statistically relevant conformations of each FFAs in eachof the systems, we determined the possible contacts with residues of the nAChR and theresulting profile of pore radius. In general, the results show that more contacts areestablished when FFAs are located in non-annular regions. As expected, contacts areestablished in a much greater proportion with non-polar residues. cis-18:1ω-11 in nonannular sites leads to conformations that open the pore of the channel, while in annularsites it stabilizes the desensitized state. With cis-18:1ω-13 a similar behavior isobserved, although in non-annular sites it produces a pronounced constriction in theextracellular domain.